Pengelolaan Laboratorium IPA Di SMP Negeri 1 Dan SMP Negeri 2 Ngemplak Kabupaten Boyolali Semester Genap Tahun Ajaran 2014/2015 - Istiqomah, Yunita; , Dra. Hariyatmi, M.Si (2015)
Science deals with how to find out the natural phenomenons systematically, so that science is not only about the mastry of some knowledges such asa the facts, concepts, or principles but also about the process of discovery (Mulyasa, 2007). Science laboratory is served as a place of learning activitiesthat requires particular equipments that can't be served in the classroom easily. The requisite of science learning is practice which is held in the laboratory. The laboratory is managed by a teacher who is appointed as a head of laboratory. This research aims to determine the abilities of the science laboratory manager of SMP N 1 and SMP N 2 Ngemplak on the even semester of 2014/2015. This is a descriptive qualitative research which is sampled with science laboratory managers of those junior highschool. The data accumulation technique such as observe the condition of the science laboratory management showed that the ability included on in the decent category (49,3%). The ability of laboratory management SMP Negeri 1 Ngemplak included on in the decent category (47,9%) and SMP Negeri 2 (50,7%) on the average, the science laboratory management in the aspects of planning stands on 0%, 50% on setting, 45,83% on administration, 75% on maintenance , 25% on safety, and 75% on security.